Supramolecular cyclodextrin-based metal-organic frameworks as efficient carrier for anti-inflammatory drugs - Abuçafy, Marina P. [UNESP]; Caetano, Bruno L. [UNESP]; Chiari-Andréo, Bruna G. [UNESP]; Fonseca-Santos, Bruno [UNESP]; do Santos, Aline M. [UNESP]; Chorilli, Marlus [UNESP]; Chiavacci, Leila A. [UNESP] (Elsevier, 2018)
Drug delivery systems have been used to reduce adverse effects and improve the efficacy of therapies. Drug carriers have been developed over the years, but they have limitations. γ-cyclodextrin-based metal-organic frameworks (γ-CD-MOF) have significant advantages due to their biocompatibility and environmental safety, besides crystallinity and porosity. Herein, γ-CD-MOFs were synthesised with different metals as nodes and investigated. Uniform mesoporous γ-CD-MOFs were obtained and showed an absence of toxicity in HepG2 and Caco-2 cells. The longer controlled release was verified for γ-CD-MOFs, with a maximum of 62% released in 12 h. An inflammation experiment was performed in mice and activity equivalent to the positive control was verified. γ-KCD-MOFs and γ-NaCD-MOFs reached activity after 6 h of administration, however this happened after 24 h in γ-FeCD-MOFs, being more effective than the positive control. Considering the ability for drug entrapment, easy preparation and controlled release, this class of material allows potential applications in drug delivery systems.
Keywords: Anti-inflammatory in vivo assay; Drug adsorption; Drug delivery; Metal-organic framework; γ-cyclodextrin